Pembelajaran IPA yang Terintegrasi Dengan PKLH Beradasarkan K 2013 Revisi Di SMP Negeri 1 Balla Kabupaten Mamasa - Rambulangi, Elisaberth; Muzaki, Muzaki; Lullulangi, Mithen (UNM Environmental Journals, 2020)
This study aims to determine the inhibiting factors for science teachers in integrating Population and Environmental Education (PKLH) with science subjects based on the 2013 Curriculum (K13 Revision) in SMP Negeri Balla District, Mamasa Regency. The population of this study were 4 science teachers in three State Junior High Schools in Balla District. Using saturated samples so that the number of samples = 4 teachers. The research variables are: 1) Teaching preparation, 2) Understanding of K 13 Revision, 3) Ability to identify PKLH material from K 13 Revision of Science subject, 4) Knowledge of PKLH material, and 5) Ability to plan, implement, and evaluate learning PKLH is integrated with science subjects. The data in this study are the results of structured interviews with respondents, quantitative descriptive data analysis techniques. The results showed that the inhibiting factors for PKLH learning in an integrated manner with science subjects at SMP Negeri Balla District were weak teachers in terms of: 1) Identifying PKLH material in K13 Revision of junior high school science subjects; 2) Planning PKLH learning in an integrated manner with science subjects; and 3) Evaluating PKLH learning in an integrated manner with science subjects.